How to Build Movements with Cyclical Patterns in Mind - Non Profit New s | Nonprofit Quarterly - Algoso, Dave; Guerzovich, Florencia; Gattoni, Soledad (Nonprofit Quarterly, 2023)
The world changes too much for anyone who is invested in social change work to imagine that this work is linear and predictable. Opportuniti es come and go, whether caused by a pandemic or political shifts. This much most social movement leaders and activists intuitively understan d. But what can be done with this realization? How might movement grou ps better prepare for moments of opportunity? We want to explore how w e can create the changes we want to see by responding to the changes t hat are outside our control.